2017
DOI: 10.3390/v9080198
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Bronchitis Virus Infection Induces Apoptosis during Replication in Chicken Macrophage HD11 Cells

Abstract: Avian infectious bronchitis has caused huge economic losses in the poultry industry. Previous studies have reported that infectious bronchitis virus (IBV) infection can produce cytopathic effects (CPE) and apoptosis in some mammalian cells and primary cells. However, there is little research on IBV-induced immune cell apoptosis. In this study, chicken macrophage HD11 cells were established as a cellular model that is permissive to IBV infection. Then, IBV-induced apoptosis was observed through a cell viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 49 publications
(58 reference statements)
2
42
0
Order By: Relevance
“…Our results showed that IBV could induce apoptosis in CEK cells (Figure 4), and increase mRNA expression levels of Fas, FasL, JNK, Bax, Caspase 3, and Caspase 8, with the exception of Bcl-2, which significantly decreased after IBV infection ( Figure 5), which was consistent with other reports (Chhabra et al, 2016;Fung et al, 2014;Liao et al, 2013). It was found that IBV could increase the mRNA expression levels of Fas, FasL, and Bax, and decrease the mRNA expression level of Bcl-2 in IBV-infected HD11 cells (Han et al, 2017). Another research demonstrated that JNK served as a pro-apoptotic protein during IBV infection.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that IBV could induce apoptosis in CEK cells (Figure 4), and increase mRNA expression levels of Fas, FasL, JNK, Bax, Caspase 3, and Caspase 8, with the exception of Bcl-2, which significantly decreased after IBV infection ( Figure 5), which was consistent with other reports (Chhabra et al, 2016;Fung et al, 2014;Liao et al, 2013). It was found that IBV could increase the mRNA expression levels of Fas, FasL, and Bax, and decrease the mRNA expression level of Bcl-2 in IBV-infected HD11 cells (Han et al, 2017). Another research demonstrated that JNK served as a pro-apoptotic protein during IBV infection.…”
Section: Discussionsupporting
confidence: 90%
“…In recent year, nephropathogenic IBVs have become prevalent genotypes in China [2], new nephropathogenic isolates induce more severe lesions to kidney and show high mortality in young chickens [3]. Currently only IBV Beaudette strain can replicate in HD11 [4] or Vero [5] cell lines. Several recent works have proved the induction of apoptosis and suppression of immune response are related to the pathogenicity of nephropathogenic IBVs [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that a group of genes involved in apoptosis were differentially regulated in chicken kidney cells while infected with IBVs of different virulence, and the intrinsic and extrinsic pathways were the main approaches to apoptosis in these cells. Interestingly, the same apoptotic pathways were detected in chicken macrophage DH11 cells [37] and endoplasmic reticulum stress was reported as apoptotic pathways in mammal vero cells when both were infected with IBV Beaudette strain [38], indicating the approach to apoptosis in chicken is different from those in mammalian Vero cells.…”
Section: Induction Of Apoptosis In Virulent Nephropathogenic Ibv Infementioning
confidence: 76%